Conditions of caring for the elderly and family caregiver stress in Chiang Mai, Thailand. Issue 2 (15th November 2018) - Tamdee, Decha; Tamdee, Patrapan; Greiner, Chieko; Boonchiang, Waraporn; Okamoto, Nahoko; Isowa, Tokiko
Abstract : Purpose: The family caregivers play an important role in the good quality of life for the elderly, but most of them can easily have an emotional and psychological effect on caregiving. The purpose of this paper is to explore the correlation between conditions of caring for the elderly in the family and caregiver stress in a community setting, Chiang Mai Province, Thailand. Design/methodology/approach: A cross-sectional exploratory descriptive research was conducted in Ban Klang Subdistrict, San Pa Tong District, Chiang Mai Province. Simple random sampling was used to collect data by using a structured interview via a questionnaire with 103 elderly caregivers. The χ 2 test was used to explain the conditions related to stress as being a caregiver. Findings: Most of the caregivers were female and still in good health, but at the same time, underwent little stress. However, they did not receive any training beforehand for taking care of the elderly but mainly done by experience, relationship and gratitude. The conditions correlated with stress as being a caregiver were health status of caregivers, confidence of care, the relationship between caregiver and elderly person, and economic burden of care. Originality/value: A necessary resource such as body of knowledge in elderly caregiving, long-term care system at the community level and social support from family and intimate persons will encourage confidence in taking care of the elderly in the family and also relieve caregivers' stress.